Associations between schistosomiasis and the use of human waste as an agricultural fertilizer in China. - Elizabeth J Carlton; Yang Liu; Bo Zhong; Alan Hubbard; Robert C Spear (Public Library of Science (PLoS), 2015)
BACKGROUND:Human waste is used as an agricultural fertilizer in China and elsewhere. Because the eggs of many helminth species can survive in environmental media, reuse of untreated or partially treated human waste, commonly called night soil, may promote transmission of human helminthiases. METHODOLOGY/PRINCIPAL FINDINGS:We conducted an open cohort study in 36 villages to evaluate the association between night soil use and schistosomiasis in a region of China where schistosomiasis has reemerged and persisted despite control activities. We tested 2,005 residents for Schistosoma japonicum infection in 2007 and 1,365 residents in 2010 and interviewed heads of household about agricultural practices each study year. We used an intervention attributable ratio framework to estimate the association between night soil use and S. japonicum infection. Night soil use was reported by half of households (56% in 2007 and 46% in 2010). Village night soil use was strongly associated with human S. japonicum infection in 2007. We estimate cessation of night soil use would lead to a 49% reduction in infection prevalence in 2007 (95% CI: 12%, 71%). However, no association between night soil and schistosomiasis was observed in 2010. These inconsistent findings may be due to unmeasured confounding or temporal shifts in the importance of different sources of S. japonicum eggs on the margins of disease elimination. CONCLUSIONS/SIGNIFICANCE:The use of untreated or partially treated human waste as an agricultural fertilizer may be a barrier to permanent reductions in human helminthiases. This practice warrants further attention by the public health community.